2003
DOI: 10.1067/mai.2003.33
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus-induced wheezing in infancy—the first sign of childhood asthma?

Abstract: Our results present rhinoviruses as important inducers of wheezing even in infancy. The association with atopy and subsequent asthma calls for reevaluation of the role of rhinoviruses in the development of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
402
3
18

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(461 citation statements)
references
References 35 publications
38
402
3
18
Order By: Relevance
“…Similar to RSV, RV-related respiratory illness during early life has also been associated with a high risk of suboptimal lung health and function later in life [100102]. Insight on the association between RV-related respiratory illnesses and the risk of future asthma originated from the Childhood Origins of Asthma Study, a prospective birth cohort of term-born infants at high risk of asthma and atopy [103].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to RSV, RV-related respiratory illness during early life has also been associated with a high risk of suboptimal lung health and function later in life [100102]. Insight on the association between RV-related respiratory illnesses and the risk of future asthma originated from the Childhood Origins of Asthma Study, a prospective birth cohort of term-born infants at high risk of asthma and atopy [103].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Hospitalisation with RV-related respiratory illness has been associated with a more than 3-fold increase in the rate of recurrent wheeze among healthy term-born infants during the following year [105]. Similarly, hospital presentation and/or admission with an RV-related wheezing illness in childhood is associated with a 3-fold increased risk of subsequent hospitalisation for another respiratory illnesses [106] as well as a more than 4-fold increased risk of subsequent asthma [100]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Moreover HRVs cause upper respiratory tract infections at all ages and are the main cause of LRTIs leading to hospitalisation in infants and young children outside of the winter RSV bronchiolitis season (Montalbano and Lemanske, 2002;Kotaniemi-Syrjänen et al, 2003;;Hayden, 2004;Korppi et al, 2004;Miller et al, 2007;Wiehler and Proud, 2007;Peltola et al, 2008;Lachowicz-Scroggins et al, 2010;Jartti and Korppi, 2011;Rollinger and Schmidtke,2011;Skevaki et al, 2012;Aya Takeyama et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since viral illnesses contribute significantly to wheezing in early life, it has been of interest to determine which viruses had the greatest potential of not only producing early life wheezing, but possibly to be associated with the subsequent development of asthma as well. In this regard, a number of evaluations in hospitalized infants indicated that respiratory syncytial virus (RSV) infections had this potential (2,3). However, with the advent of advances in molecular viral technology, it has now been possible to evaluate the contribution of other viruses to asthma development as well.…”
Section: Who Is the Right Patient?mentioning
confidence: 99%